Carbohydrate ingestion did not affect 60 km self paced cycling performance during exercise in the heat - Nassif, C.; Gomes, A.; Soares, D.; Cannon, J.; Silami-Garcia, E.; Marino, F. (Journal of Science and Medicine in Sport, 2011)
Introduction: The effect of carbohydrate (CHO) supplementation on endurance performance has been extensively studied but its placebo (PLA) effect can make the ergogenic qualities of CHO more difficult to determine. This study tested the effect of double blind ingestions of PLA and 6% CHO in capsules (c) and in a beverage (b) during a 60 km self-paced cycle time trial in the heat (32 oC and 50% relative humidity). Methodology: Ten well trained male subjects (means 26 years old, range 22 - 31; 64 kg of body weight, range 55 - 77 and 71 mL/kg.min maximal oxygen consumption, range 53 - 80) completed 5 x 60km cycling time trials (TT) punctuated with 4 x 1 km sprints at 14, 29, 44 and 59 km in a 5 x 5 latin square design. Trials consisted of 5 treatments, PLA in beverage (PLAb) and capsule (PLAc) form and CHO (CHOb and CHOc) in similar forms and a control water trial (H2O). Beverages or capsules were ingested at 5 km, after each sprint and at 55 km. Each subject received an average of 284 mL of distilled water and capsules (4 mL/kg of body mass) or beverage depending on the treatment. The amount of CHO and PLA powder in capsules was calculated to match the volume of water so that the mixture of the water and powder or water and capsules would correspond to a 6% CHO solution. The mean number of capsules consumed during each treatment was 116 for PLAc and for CHOc. Thus, the mean number of capsules per ingestion was 24. Statistical analyses were performed using a 5 x 1 factorial ANOVA with repeated measures. Where a significant main effect was observed, a LSD post-hoc test was used to identify the source of significance. Results and Conclusions: There were no differences in TT among treatments (means H2O 138 min, range 117 - 181; PLAb 130 min, range 109 - 151; CHOb 140 min, range 110 - 161 ; PLAc 143 min, range 114 - 220 and CHOc 137, range 108 - 148). An increase in blood glucose was observed in the treatments where CHO was ingested compared with PLA and H2O treatment (p< 0.05). It is concluded that CHO ingestion independent of the mode of ingestion, either capsule or beverage, did not affect prolonged self paced cycling performance compared to either PLA or H2O.